How Is It Done: A Qualitative Analysis of Teachers Strategies in Meeting the Challenges of Differentiated Instruction - Juwita, Ratna; Sukmawati, Fatma; Santosa, Eka Budhi; Cahyono, Budi Tri; Prihatin, Relly; Suparmi, Suparmi (JTP - Jurnal Teknologi Pendidikan, 2024)
Differentiated Instruction (DI) is considered an important but challenging task which many teachers feel unprepare. A list of requisite skill of DI is needed to eliminate teachers’ unpreparadness. This study aimed to explore requisite skills for DI implementation and to identify best practices across various school levels. Using 112 self-reported essays, subsequent interviews, videotaped DI practices, and experts meeting, this article employed Cognitive Task Analysis (CTA) to capture a description of the knowledge that experts use to carry out differentiations. The result revealed that CTA of DI implementation contained four essential skills in the preparation phase, nine skills in the implementation phase, and two skills in the evaluation phase. Despite of highly different contexts of school levels, this study found similarities in DI practices across all levels. This study contributes to the existing body of knowledge on DI by highlighting the effectiveness of CTA in identifying and implementing DI strategies across different educational levels. Future research should explore the long-term impacts of DI on student achievement and engagement, as well as investigate DI practices in different educational settings.